Putting Canada in a Comparative Context: Still the Multiculturalist Unicorn. Issue 3 (2nd July 2016) - Mudde, Cas
Abstract : In a very respectful response—titled with a classic rhetorical question: "Does Canadian Multiculturalism Survive through State Repression?"—Phil Ryan supports most of the arguments that Emma Ambrose and I laid out in our article "Canadian Multiculturalism and the Absence of the Far Right." However, he does question two particular claims: (1) that the Canadian state represses critique of multiculturalism and (2) that there are no other supply-side factors to explain the absence of the far right in Canada. In this short response, I will argue, first and foremost, that Ryan perceives Canada too much through an exclusively Canadian lens, exaggerating the tolerance of the Canadian state for far-right discourse as well as the criticism of multiculturalism by the Conservative Party of Canada.